Impact of NOx Emissions Released from a Gas Turbine-Based Power Plant on the Ambient Air Quality. Issue 1 (2nd January 2019) - Abdul-Wahab, Sabah; Fadlallah, Sulaiman; Alnaamani, Almundher
Abstract: The number of gas turbine- (GT-) based power plants is rapidly increasing to meet the world's power demands. Until a few years ago, fossil fuel, and specifically fuel oil, was considered the major energy source for gas turbine operation. Due to the high amount of pollution that fuel oil generates, natural gas has become a popular source of energy due to its lower emissions compared to fuel oil. As a result, many GTs have switched to natural gas as an alternative to fuel oil. However, pollutants expelled from GT-based power plants operating on natural gas impact surrounding air quality. The objective of this study was to examine the dispersion of nitrogen oxides (NO x ) emitted from a GT-based power plant located in the Sultanate of Oman. Supported by CALPUFF dispersion modeling software, six scenarios were investigated in this study. The first four scenarios considered a case where the GT-based power plant was operating on natural gas during winter and summer and for open and combined cycle modes. The remaining two scenarios considered, for both open and combined cycle modes, the case where the GT-based power plant was operating on fuel oil. Whether run by natural gas or fuel oil, CALPUFF simulation results for both seasons showed that NO x concentrations were higher when GTs were used in the combined cycle mode. The concentrations were still lower than the allowable concentrations set by the United States Environmental Protection Agency (U.S. EPA) standards. In contrast, for the case where the power plant operated on fuel oil, the NO x one-hour average simulated results exceeded the allowable limits only when the combined cycle mode was activated.